On compliance with the rules of legal technology in the Civil Code of the Republic of Kazakhstan - Tokatov, R.A.; Oralbayev, N.K. (Bulletin of the Karaganda University “Law Series”, 2021)
The most important sign of the independence of the state is its language and centuries-old national culture. The sovereignty of the country is inextricably linked with the language, mentality and religion of the people. If the problem of the native language loses its place in public relations in the state, then the state and national security may remain without a future. In this regard, the place and importance of the Kazakh language in the legal sphere is one of the most reasonable questions. What will be the future of the country if we regulate public relations with illiterate or translated laws? As a scientific method in the article the methods of combining legal techniques and theoretical methods from the abstract to the concrete were used. The object of the study is carried out in accordance with civil legislation in the form of applying research methods and comparing mistakes made in the adoption and translation of specific legal norms in force. The work on identifying errors and conflicts was carried out by means of control in the comparative method of the norms set out in the Russian and Kazakh languages. In the course of the research work, real gaps and contradictions in the field of civil legislation are identified, cases of incorrect application of the rules of legal technology in the formation of norms are described.